2004
DOI: 10.1532/hsf98.20041015
|View full text |Cite
|
Sign up to set email alerts
|

A Long-term Porcine Model for Evaluation of Prosthetic Heart Valves

Abstract: A practically feasible long-term porcine model of MVR has been established. Because the pig is superior to other species with respect to anatomical and physiological similarity to humans, we consider this model as an optimal platform for experimental preclinical testing of heart valve prostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…Another potential disadvantage of the standard mitral valve model is the risk of developing periprosthetic leak secondary to somatic growth [20]. We tried to avoid this problem by maintaining the animals on a strict caloric intake to maintain preoperative weight throughout the duration of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential disadvantage of the standard mitral valve model is the risk of developing periprosthetic leak secondary to somatic growth [20]. We tried to avoid this problem by maintaining the animals on a strict caloric intake to maintain preoperative weight throughout the duration of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Though many research groups use calves, canine or ovine species for CHF investigation (19), studies of human and porcine heart size and morphology, heart valves, hemodynamics and coronary anatomy have shown remarkable similarities, rendering the porcine species superior with respect to human compatibility (20). Furthermore, our research group has previously shown that it is possible to use pigs for large animal models with an acceptable mortality rate, and a well functioning setup for pre-and postoperative care, and follow-up examinations (10,21).…”
Section: Discussionmentioning
confidence: 99%
“…The operative technique and anaesthetic treatment have been described elsewhere [10,11]. In brief, the pigs were sedated, intubated, and a median sternotomy was performed.…”
Section: Aortic Valve Implantationmentioning
confidence: 99%